Effect of build orientation on the green tribological properties of multi-jet fusion manufactured PA12 parts - Gavcar, Beyza; Sumer, Emir Halit; Sagbas, Binnur; Katiyar, Jitendra Kumar (SAGE PUBLICATIONS LTD, 2023)
Additive manufacturing (AM) is a newly developed technology for manufacturing parts from three-dimensional (3D) computer-aided design (CAD) models by depositing a material layer on layer. Multi-jet fusion (MJF) is one of the AM technologies that can be used for manufacturing functional parts like gear, linear, bearing, etc., by polymers. In various applications, technical processes, design of tribological systems, optimum lubrication, and reduction of wear and friction are significant performance criteria to provide energy and material conservation. The development of green tribological applications offers essential solutions to problems of ecosystem pollution and energy from a global point of view to increase sustainability. In this article, the green tribological behavior of Polyamide 12 (PA12) parts, manufactured by MJF with different build orientations was evaluated by ball-on-disc tribological tests under different normal loads and lubricated environments. Mechanical profilometer and digital microscope were used to evaluate surface quality and morphology. Scanning electron microscope (SEM) was used to determine the samples' wear characteristics. The maximum surface roughness was measured for the part having a build orientation of 45 degrees. The maximum coefficient of friction value was determined as 0.355 for the sample with 45 degrees orientation under 5 N load and dry environment. The maximum wear rate value was determined as 2.3249 x 10-4 mm3/Nmm for the sample with 0 degrees orientation under 10 N load and dry state. The differences between build orientations should be considered when evaluating tribological properties. This article provides a new perspective to researchers and practitioners toward green tribology of polymer AM parts.
Keywords: Additive manufacturing; build orientation; multi-jet fusion; green tribology; lubrication; polyamide 12; PALM OIL; SURFACE QUALITY; PERFORMANCE; IMPROVEMENT; PARAMETERS; RESISTANCE; LUBRICANTS; POLYMERS; FRICTION; Engineering